Mobilizando-se para resgatar a vida através do implante coclear: a experiência da família da criança com deficiência auditiva - Vieira, Sheila de Souza (2011)
This work scoped to comprehend the experience of the cochlear implant user auditive deficient child‟s family, more precisely to understand its role, identify the changes into the everyday life, describe the strategies which are in between the cohabiting with the auditive deficiency in the childhood, and, to acknowledge the structure, the development and the family functionality. This research is about a qualitative work having the Symbolic Interactionism and a The Grounded Theory as theoretical and methodological references respectively. To obtain the data we used genogram, ecomap and consented interview semistructured. Nine families participated in the study, reaching a total of 32 participants. The data analysis permitted us build up seven thematic categories: In seeing an idealized future pulling down, Seizing to the hope of implanting, Battling for results, Facing hard moments, Recognizing that she doesn t face it all alone, Learning to overcome, and Having the life rescued by the cochlear implant, which compose the phenomenon: MOBILIZING TO RESCUE THE FAMILY LIFE THROUGH THE COCHLEAR IMPLANT, by which we comprehend this experience. We learnt that the implant altered the path of their lives and it permitted the family resignify the deafness. It is like a passport which makes possible to the child to live in the world with less difficulties, more independency and autonomy, and with more chances of a personal, social, academic and professional future of success like any other child. The results show us that it is indispensible to make the family participate actively into the child‟s linguistic development and let the communication skill be worked, for its role as protagonist in the process of rehabilitation and constant stimulation showed us to be evident. We expect that this work may help and conduct the professionals involved in the area to care for the families of auditive deficient children, specially the implanted ones, taking into account the familiar perspective in its professional practice. And we make an invitation to the Nursing Field to approach those families into the reality and to the complexity of the experience of the cochlear implant in the childhood, in order to appropriate the knowledge of this issue, act and exercise their practices.